An approach to evaluation and selection of business core processes - Pendić Zoran R.; Pendić-Polak Sanja Z.; Jakovljević Bojana B.; Polak Marko M.; Lačnjevac Časlav M. (Tehnika, 2020)
The traditional management is hierarchically organized. The transition from traditional management to process management requires a radical shift in thinking from a command-and-control, personality based, top-down hierarchy to horizontal, process-oriented, team-oriented structure. Business model of an organization, implementing business process management, is realized through a network of processes. The goal of business process management is to systematically improve all processes, espesially core processes. Core processes are work processes that cross functional boundaries, produce an output that is strategically important to the organization's success and are essential for organization survival at market. Very often an organization has a set of busness processes which are improvement candidates. The problem is how to choose the set of processes whose performance improvement will do the best for organization at all. In this paper an approach for evaluation and selection of core processes is presented. The proposed approach is based on process' objects and the three-level hierarchical quality evaluation model.